National review of maternity services 2008: women influencing change - Francis Karen; McIntyre Meredith J; Chapman Ysanne (BMC, 2011)
Abstract Background In 2009 the Australian government announced a major program of reform with the move to primary maternity care. The reform agenda represents a dramatic change to maternity care provision in a society that has embraced technology across all aspects of life including childbirth. Methods A critical discourse analysis of selected submissions in the consultation process to the national review of maternity services 2008 was undertaken to identify the contributions of individual women, consumer groups and organisations representing the interests of women. Results Findings from this critical discourse analysis revealed extensive similarities between the discourses identified in the submissions with the direction of the 2009 proposed primary maternity care reform agenda. The rise of consumer influence in maternity care policy reflects a changing of the guard as doctors' traditional authority is questioned by strong consumer organisations and informed consumers. Conclusions Unified consumer influence advocating a move away from obstetric -led maternity care for all pregnant women appears to be synergistic with the ethos of corporate governance and a neoliberal approach to maternity service policy. The silent voice of one consumer group (women happy with their obstetric-led care) in the consultation process has inadvertently contributed to a consensus of opinion in support of the reforms in the absence of the counter viewpoint.